(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hip implants are common and diversified types of metals are used for hip implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Toxicity of hip-implants”. All published articles related to “Toxicity of hip-implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “Toxicity of hip-implants” and also to find out the trends related to the same. The most active journals in this research domain were the Journal of Bone and Joint Surgery. The most active country was the United States of America. The leading organization engaged in the research regarding the toxicity of hip-implants were the Rush University Medical Center of United States of America and the University of Strathclyde of Scotland. The most active authors who had made valuable contributions related to the toxicity of Hip implants were Grant M.H, Jacobs J.J, Catalani S, and Apostoli P.